The Effect of Product Display and Store Atmosphere on Impulse Buying in Consumers Mandiri Store Gresik - Rini Purwati; Sumainah Fauziah (Universitas KH. Abdul Chalim Mojokerto, 2025)
The development of business in Indonesia is increasing every year, leading to tighter competition among industries, particularly in the retail sector. This situation demands that consumers pay close attention to changes in meeting their daily needs. Toko Mandiri Gresik has become a primary destination for the local community to fulfill various personal and family needs. This research aims to determine the impact of product display and store atmosphere on impulse buying among consumers at Toko Mandiri Gresik. The population for this study consists of individuals who have made purchases at Toko Mandiri Gresik at least twice in the last three months, are at least 17 years old, and live in Gresik. The study uses a sample of 90 respondents selected through non-probability sampling methods, specifically purposive sampling. Multiple linear regression analysis is employed to analyze the data using SPSS version 25. The results indicate that product display influences impulse buying, store atmosphere affects impulse buying, and both product display and store atmosphere significantly impact impulse buying.